(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article conception of existence is considered in the history of philosophical thought. In modern philosophy, structure and essence of ontological science has logical basis; reality is viewed as one single entity, independent from cognitive activity of a human. Questions of ontology formed into a free-standing study of various multi-faceted studies of nature in the early ancient Greek philosophy. Interest for ontology was arisen in XVII century when philosophy was transforming from the place of «theology servant» into self-contained intelligence based science. Metaphysical view on ontology was overcome in Classic German philosophy in XIX century. Appearance of new studies of existence is associated with such prominent names as E. Husserl, M. Heidegger, J.-P. Sartre and other philosophers of XX century. The problem of existence in the century-old history of philosophy has experienced dramatic evolution. Reason of life and place of a human in the world: these are the questions with no definite answer. Key words: ontology, being-in-the-world, existence, entity